(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
One of the topical issues of the article is a conceptual change in the structure of khokimiyats based on the creation of service units, the criteria necessary for the provision of high-quality and full-fledged public services; official approval of the list of public services for which khokimiyats are directly responsible; granting khokimiyats the right to negotiate and conclude agreements with economic entities on the provision of part of public services by the private sector; dedicated to the development of an integrated website that can receive and respond to inquiries from the public and provide sufficient information about related services.